Balanço energético negativo modula a expressão de ISG15 no endométrio e corpo lúteo durante o reconhecimento materno da gestação em ovinos - Zappe, Igor Gabriel (2020)
Embryonic mortality during maternal recognition of pregnancy is a major cause of reproductive failure in ruminants. One of the causes of reduced fertility in ruminants is the occurrence of a negative energy balance (NEB). The hypothesis of this study is that NEB may influence the occurrence of poor maternal-embryonic communication, impairing maternal recognition of pregnancy. The aim of our study was to evaluate the effects of NEB on the expression of ISG15 in the endometrium and corpus luteum on day 17 of gestation. For this, 21 crossbred Texel-Corriedale ewes had estrus and ovulation synchronized and 18 mated. The ewes were allocated into four experimental groups: non-pregnant, non-bred control group (CNP, n = 3); pregnant control group (CP, n = 6); NEB group during the first week of embryonic development (FW; n = 6); and NEB group during the second week of embryonic development (SW; n = 6). The ewes in the FW group fasted from days 0 to 7 and the ewes in the SW group fasted from days 9 to 16 for the induction of NEB with hyperketonemia. BEN was induced in two distinct stages of embryonic development: first week of embryonic development and second week of embryonic development. During the experimental period, the blood levels of β-hydroxybutyrate (BHBA) and glycemic levels were measured. On day 17 of the estrous cycle or gestation, the sheep were euthanized and samples of the endometrium and corpus luteum (CL) were collected. The relative expression of ISG15 was assessed by q-PCR. Animals that had NEB induced had a reduction in glycemic levels and an increase in BHBA blood levels. Pregnant ewes had higher ISG15 relative expression of than non-pregnant ewes in endometrium from ipsilateral horn at ovulation and in the CL. The CP group had greater expression of ISG15 than the CNP group in the endometrium from ipsilateral horn at ovulation and in the CL. The FW and SW groups showed no difference in the ISG15 relative expression of the CNP and CP groups in the endometrium from contralateral and ipsilateral horn at ovulation. The FW group had a higher ISG15 relative expression than the CNP group in the CL. In conclusion, ewes that had periods of NEB during embryonic development, especially during the second week of embryonic development, had a lower ISG15 relative expression, with no difference in the ISG15 relative expression in the endometrium from contralateral and ipsilateral horn at ovulation when compared with the CNP.